Pengembangan Modul Pembelajaran Pada Materi Dinamika Rotasi Terintegrasi Alat Eksperimen Berbasis Mikrokontroler Arduino Untuk Melatih Keterampilan Berpikir Kritis Siswa SMA - Fauza, Naila; Moga Sahid, Ridha Nurthaybah; Sahal, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teaching rotational dynamics requires innovative instructional materials to develop students’ critical thinking skills. This study aims to determine the validity and practicality of a rotational dynamics learning module integrated with a microcontroller-based experimental tool. The method used in this study is research and development using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The instruments used were validity and practicality checklists. The results of the research on the development of the rotational dynamics learning module integrated with a microcontroller-based experimental tool showed a total average validity score of 0.89, categorized as valid, and an average practicality score of 3.4, categorized as practical. Based on the research results, the rotational dynamics learning module integrated with a microcontroller-based experimental tool is suitable for use.